Ruta Turística de los recursos naturales y culturales del Cantón Espíndola, Provincia de Loja - Medina Piedra, Pablo David (2018)
Ecuador, a country located in the center of the world, enjoys a great biodiversity embodied in its 4 natural regions, and also has historical attractions, gastronomic and a variety of cultures, traditions giving as a result of this a Country with a vast natural and cultural richness. The province of Loja is carrying out projects that allow to increase the tourist offer and at the same time improve the natural and cultural part, which is not being valued and harness properly. Within the province of Loja is located the Canton Espindola, better known as the "Land of enchanted Orchids and lagoons", of the same name as the main river that irrigates the very rugged geographical territory, which gives, as a result a magical garden of natural landscapes, shaped mountains, plateaus, small valleys lively and full of vegetation. From this point of view it was important to develop the research work on "TOURIST ROUTE OF THE NATURAL AND CULTURAL RESOURCES OF THE CANTON ESPINDOLA, PROVINCE OF LOJA", for which it was proposed as a general objective, "Design a tourist route of the natural and cultural resources of the canton Espindola, province of Loja", in correlation with this, specific objectives were raised; Carry out the tourist diagnosis of the natural and cultural resources of the Espíndola canton, Loja Province; Propose the design of the tourist route of the natural and cultural resources of the canton Espíndola, province of Loja; with the actors involved in the investigation. Within the methodology used, for the fulfillment of the first objective was used the analytical method the same that made it possible to carry out an analysis of the environment of the attractions of the Canton; for the tourist diagnosis the Matrix of Carla Ricaurte was used and also there took as main sources the practices, thesis and works investigative and other studies that rest in the National University of Loja and the Municipal GAD and authorized web pages, so that reliable information was obtained from the Canton, also there was used the technique of the direct information using the card of tourist attractions of the MINTUR, as well as interviews to those involved in the tourism topic of the canton. To fulfill the second objective, the importance of the attractions to be considered for the route was determined, using the MINTUR methodology and annexes of the fieldwork during the visit to the attractions. For the design of the route were used computer programs such as MAP Source, Google maps, etc. like also some bibliographic references. The proposal of the route was supplemented with a dash and design of promotional material as a poster, folding, CD consisting of a video and a musical composition. For the fulfilment of the third objective was convened to the socialization of the results to the authorities and population of the canton which directly or indirectly collaborated with the development of the investigation, being used in this objective the technique of MARPP. With the culmination of the investigation, it is concluded that the canton Espíndola account with a great variety of natural and cultural resources, the same ones that constitute tourist attractions with an impressive potential which must be used for the tourist development by the community, likewise with the creation of the tourist route, the community will be sensitized, on the importance of the tourist theme, the same one that will allow the economic and social development, in the same way it was possible to note the great importance that this route has for the canton, so it constitutes a first in the tourist development of the canton, being an inspiration to new horizons of future projects, all this with the welfare of the community. The recommendations are addressed to the authorities of the autonomous Municipal government of Espindola, which are to include in the archives the route, in order to constitute a source of truthful information, also initiate awareness campaigns and dissemination aimed at the general public of the canton, to commit itself to care for and make known the resources natural tourist and cultural giving them the importance deserved. It is very important to implement a tourism department in the canton, and to execute in an immediate way the present proposal, the same one according to the results of the research, will offer the optimization of the tourist activity of the canton